ChemInform Abstract: Enantioselective Synthesis of 3‐Fluoro‐3‐allyl‐oxindoles via Phosphine‐Catalyzed Asymmetric γ‐Addition of 3‐Fluoro‐oxindoles to 2, 3‐Butadienoates. Issue 42 (October 2015) - Wang, Tianli; Hoon, Ding Long; Lu, Yixin
Abstract The addition product can be easily converted into the 3‐allyl substituted oxindole derivative (V).